Validity and Internal Consistency Reliability of a Computerized Test to Assess Prone Extension in Children Ages Four to Six Years. - Lin, Chin-Kai; Wu, Huey-Min; Kuo, Bor-Chen; Li, Cheng-Hsaun (Perceptual & Motor Skills, 2010)
The objective of this study was to develop a computerized test of prone extension to measure performance of prone extension in children 4 to 6 years of age. The participants were selected from kindergartens, comprising 132 boys and 107 girls with a mean age of 5 yr. 2 mo. (SD = 6 mo.). Sensitivity and specificity of the computerized test of prone extension were assessed by comparison with the judgments of an expert, an occupational therapist with more than 20 yr. of pediatric experience, as the criterion standard. The computerized test of prone extension identified children with poor outcomes with a sensitivity of 0.83, a specificity of 0.88, and an accuracy of 0.87. The internal reliability index was 0.81. The computerized test of prone extension could be of value in detecting problems of antigravity posture in prone extension and permitting early intervention to correct it. Reprinted by permission of the publisher.